Simulations to study and optimize the aberrations caused due to lenslet arrays in 3D imaging - Lian, Xiaobin (2016)
Gratings are fundamental and important elements in optical metrology. Especially when it comes to the dispersion, gratings will far excel over prisms. In optics, diffraction gratings refer to optical components with a periodic structure. They can be employed to split light and diffract light into several beams, which will direct to different angles. Both the wavelength of the light and the spacing of the gratings will affect the direction of these beam after diffraction. Therefore, the gratings can be employed as dispersive element and they are widely used in spectrometers and monochromators. The purpose of this project is to study the best combination of gratings to be used in astronomical telescope. Although the Amici prisms have largely improved prisms’ dispersion, gratings still excel over prisms on dispersion function. Therefore, our principal interest is to use Amici prism as a reference to figure out the methodology to obtain optimal aberration. The project was conducted first by the deviation of formulas in optical or gratings, followed by assumptions of the possible arrangements and their theoretical results based on simulation on Python codes and finally demonstrated by a serial of experiments.